Cyclocoelidae do Brasil (Trematoda) - Lima, Berenice Maria Fernandes (1980)
ln order to extend the knowledge concerning parasite helminths recovered from Brazilian birds, some trematodes under Cyclocoelidae Kossack, 1911 are studied. Cyclocoelum (Cyclocoelum) mutabile (Zeder, 1800) Stossich, 1902, Cyclocoelum (Cyclocoelum) phasidi Stunkard, 1929, Cyclocoelum(Haematotrephus)vanelli (Rudolphi, 1819) Dubois, 1965, Cyclocoelum (Haematotrephus) brasilianum Stossich, 1902, Ophthalmophagus magalhaesi Travassos, 1921, Typhlocoelum cucumerinum (Rudolphi, 1809) Stossich, 1902 and Neivaia cymbium (Diesing, 1850) Dubois, 1959. Cyclocoelum(Cyclocoelum)mutabile, Cyclocoelum(Cyclocoelum) phasidi and Cyclocoelum(Haematotrephus)vanelli are referred in Brazil for the first time, and consist new host records. Neivaia cymbium is also referred in four new hosts. Original camera lucida drawings of the studied species as well as a table with their geographical distribution are presented. The systematical classification of the studied family is also brought up to date.